Guts & glory : World War II - Thompson, Ben, 1980- (Thompson, Ben, 1980- Guts & glory., 2016)
From massive aerial battles that clouded the skies with planes to deathly secret operations deep behind enemy lines, the events of World War II are some of the most awe-inspiring of all time. Discover legendary commanders, tremendous fights, elite soldiers, and courageous individuals whose deeds truly made the difference in this jaw-dropping guide to the biggest war the world has ever seen.